2014
DOI: 10.1111/1469-0691.12363
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem resistance and mortality in patients with Acinetobacter baumannii infection: systematic review and meta-analysis

Abstract: Acinetobacter baumannii has emerged as a major cause of healthcare-associated infections. Controversy exists as to whether antimicrobial resistance increases the risk of mortality. We conducted a systematic review and meta-analysis to examine this association. We searched MEDLINE and EMBASE databases up to May 2013 to identify studies comparing mortality in patients with carbapenem-resistant A. baumannii (CRAB) vs. carbapenem-susceptible A. baumannii (CSAB). A random-effects model was used to pool Odds Ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
158
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(176 citation statements)
references
References 33 publications
12
158
1
5
Order By: Relevance
“…In A. baumannii infections resistant to carbapenem, mortality is higher than those with susceptibility to carbapenem. [12] The present study also found higher mortality in patients who received colistin-carbapenem combination. This increased mortality may have resulted either from the failure to achieve the desired synergistic effect after administration to severely infected patients or from the addition of infections by other resistant microorganisms developing under carbapenem.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In A. baumannii infections resistant to carbapenem, mortality is higher than those with susceptibility to carbapenem. [12] The present study also found higher mortality in patients who received colistin-carbapenem combination. This increased mortality may have resulted either from the failure to achieve the desired synergistic effect after administration to severely infected patients or from the addition of infections by other resistant microorganisms developing under carbapenem.…”
Section: Discussionsupporting
confidence: 74%
“…[1,11,12] Pneumonia is the most common type of infection; its mortality rate can increase up to 65% [4,13] when attributed to MDR-AB. In our ICU, the mortality rate was 83.6% in 134 patients with MDR-AB-associated pneumonia/VAP.…”
Section: Discussionmentioning
confidence: 99%
“…This resistance includes non-susceptibility to carbapenems, and hence the bacteria are called carbapenem-resistant A. baumannii (CRAB). The appearance of CRAB has substantially reduced the numbers of antibiotics available for treatment, and patients with CRAB infections have a significantly higher risk of mortality [3]. The global occurrence of CRAB is an escalating public health challenge, especially in South and Southeast Asia, where such strains are becoming one of the predominant nosocomial pathogens [4].…”
Section: Introductionmentioning
confidence: 99%
“…Carbapenem resistance in Acinetobacter baumannii (CRAB) infection has become increasingly prevalent worldwide and has been associated with high mortality rate (1)(2)(3). Patients with ventilator-associated pneumonia (VAP) caused by carbapenem-resistant CRAB, the incidence of which has been rising substantially, may be predisposed to poor outcome because of limited therapeutic options and the likelihood of inappropriate empirical antibiotic therapy (4,5).…”
Section: Introductionmentioning
confidence: 99%